2006
DOI: 10.1111/j.1471-4159.2006.04056.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased brain damage and curtailed inflammation in transcription factor CCAAT/enhancer binding protein β knockout mice following transient focal cerebral ischemia

Abstract: CCAAT/enhancer binding protein b (C/EBPb) is a leucinezipper transcription factor that regulates cell growth and differentiation in mammals. Expression of many pro-inflammatory genes including the cytokine interleukin-6 is known to be controlled by C/EBPb. We report that focal cerebral ischemia induced by transient middle cerebral artery occlusion (MCAO) significantly increases C/EBPb gene expression in mouse brain at between 6 and 72 h of reperfusion. To understand the functional significance of C/EBPb in pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 58 publications
6
108
0
Order By: Relevance
“…For example, as C/EBPb promotes neutrophil activation and heightened inflammation, it is not surprising that C/EBPb lossof-function is neuroprotective after focal stroke. 36 This observation does not however negate the possibility that C/EBPb could have entirely different effects on cell autonomous survival and repair of neurons. It is likely that differences in the mechanism of injury, severity of the stimulus and timing will determine which of these opposing activities dominate within ischemia-sensitive structures like the CA1 field of the hippocampus.…”
Section: Resultsmentioning
confidence: 76%
“…For example, as C/EBPb promotes neutrophil activation and heightened inflammation, it is not surprising that C/EBPb lossof-function is neuroprotective after focal stroke. 36 This observation does not however negate the possibility that C/EBPb could have entirely different effects on cell autonomous survival and repair of neurons. It is likely that differences in the mechanism of injury, severity of the stimulus and timing will determine which of these opposing activities dominate within ischemia-sensitive structures like the CA1 field of the hippocampus.…”
Section: Resultsmentioning
confidence: 76%
“…Although Cebpb expression is generally induced in response to physiological stress, including hypoxia and inflammation in several tissues and cell types, Cebpb Ϫ/Ϫ mice in which C/EBP␤-dependent gene regulation has been abrogated display a paradoxically improved response to both ischemic stroke (28) and inflammatory steatohepatitis (29), presumably because both the pro-and antiinflammatory effects of C/EBP␤ action have been blocked systemically. More subtle perturbations, such as the one used in the present study, will be necessary to tease out various tissue-specific and …”
Section: Discussionmentioning
confidence: 99%
“…SOCS acts as a negative feedback regulator and inhibits further JAK and STAT phosphorylation, thus preventing the upregulation and binding of cytokines to their receptors after an acute CNS insult (33,67). Our recent studies showed that focal ischemia induces a massive upregulation of IL-6, which increases the phosphorylation of the JAK2 and STAT3 isoforms in the ischemic hemisphere (68,69,123). Although physiological levels of STAT3 activation are essential for normal cellular functions, its excessive phosphorylation as seen after focal cerebral ischemia is neurotoxic.…”
Section: Ppar-gamma-independent-mechanismsmentioning
confidence: 99%
“…Transcriptional activation can be viewed as a double-edged sword since individual transcription factors can induce either neuroprotective or neurotoxic genes. Recent studies have shown that transcription factors like interferon regulatory factor (IRF)-1, signal transducer and activator of transcription (STAT)-3, nuclear factor (NF)-kappaB, CCAAT/ enhancer binding protein (C/EBP)-beta and early growth response (EGR)-1 promote inflammatory gene expression and thus precipitates severe neuronal damage (60,69,123,128,129). On the other hand, the activation of transcription factors like nuclear factor-E2 related factor (Nrf)-2, peroxisome proliferator-activated receptor (PPAR)-alpha and PPAR-gamma, cAMP response element-binding protein (CREB) and hypoxia-inducible factor (HIF)-1 have been suggested to be neuroprotective since they curtail oxidative stress and inflammatory gene expression (33,52,107,114,122).…”
Section: Role Of Transcription Factors In Post-ischemic Inflammationmentioning
confidence: 99%